KARAKTERISTIK BUAH DAN MUTU MORFO-FISIOLOGIS BENIH LONKIDA (Nauclea orientalis L.) DARI HABITAT ALAMI DI SULAWESI TENGGARA - Faisal Danu Tuheteru; Cecep Kusmana; Irdika Masyur; Iskandar Iskandar (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2014)
Lonkida (Nauclea orientalis L.) is a native multipurpose tropical tree species in Indonesia, which a few information regarding its biology and ecology. An experimental research was carried out to examine characters of fruit, seed and seed quality of lonkida growing at different habitat in South East Sulawesi. Fruit and seed was collected from four habitat types, such as dry land, permanent swamp, temporary swamp and temporary swamp savanna. The parameters to be observed were fruit size, seed size and morpho-physiology seed quality. The results showed that fruit size and number of seed per fruit are significantly different among habitats. The mean of fruit’s length and width and number of seed per fruit originated from permanent swamp and temporary swamp is greater than that of fruit’s from lonkida stand growing in the remain habitat’s. Those parameters ranging from 4.99±0.17 to 6.66±0.19 cm for fruit length and 3812±519 to 13.984±1912 seed for number of seed per fruit. Beside, the habitat condition also significantly affected to the characters of seed dimension and seed quality. Permanent swamp was a habitat with seed size and seed weight lower compare to another habitats. However, seeds produced by the lonkida stand growing on permanent swamp habitat and temporary swamp savanna has the higher percent of germination, germination capacity and mean day germination (MDG) than that of the seeds from lonkida stand growing on other habitats. Seed length is positively correlated with seed width and negative correlation with means germination time.